Identification of potential ibrutinib combinations in hematological malignancies using a combination high-throughput screen. Issue 4 (3rd April 2018) - Schaffer, Michael; Chaturvedi, Shalini; Davis, Cuc; Aquino, Regina; Stepanchick, Emily; Versele, Matthias; Liu, Yang; Yang, Jennifer; Lu, Rongzhen; Balasubramanian, Sriram
Abstract: Matrix high-throughput screening (HTS) methods are increasingly employed to rapidly define potential therapeutic drug combinations. We used combination HTS to identify compounds showing synergistic anti-proliferative activity with ibrutinib, an irreversible, small-molecule inhibitor of Bruton's tyrosine kinase. The goal was to identify ibrutinib combinations with maximum synergistic effects in heme malignancy lines, particularly in non-Hodgkin lymphoma including diffuse large B-cell lymphoma (DLBCL). Growth inhibition (GI) was used to measure cell viability; synergy scores characterized strength of synergistic interaction. Single-agent ibrutinib demonstrated varying degrees of activity across 30 cell lines evaluated. In DLBCL lines, TMD8 was the most sensitive to ibrutinib (GI50  = 0.001); combinations with BCL-2 inhibitor ABT-199, and PI3K inhibitors IPI-145 and GDC-0941 showed the strongest synergistic activity. Anti-proliferative synergies were also observed with BET bromodomain inhibitor (+)-JQ1, XPO1 inhibitor selinexor, and IRAK4 inhibitor, and confirmed using apoptosis assay. These findings are intended to inform and advance treatment of B-cell malignancies.